The Effect of System Quality, Information Quality and Service Quality on Use Intensity and Satisfaction of Integrated Academic Information System (SIAT) Users in Gorontalo State University - Rizan Machmud (AIBPM Publisher, 2018)
Information technology is very crucial at this time where almost all forms of business use information technology. One form of use of information technology is a product made from the Information and Communication Technology Technical Implementation Unit (UPT TIK) of Gorontalo State University (UNG), namely the Integrated Academic Information System (SIAT). SIAT is currently running for eight years in all faculties in UNG, but no research has been conducted on the level of satisfaction of its use of SIAT products. Using the DeLone and McLean (2003) model, this research was conducted to examine the satisfaction of SIAT users in terms of system quality, information quality and service quality and the intensity of the use of SIAT. Explanatory research methods with survey approaches are carried out. Data collected as many as 386 data from 500 data distributed by stratified random sampling method. Data were analyzed by PLS-SEM to test the hypothesis. The results showed that system quality had no significant effect on the intensity of use of SIAT, information quality and service quality had a significant effect on intensity of use, then when the intensity of use was intensely used by users, user satisfaction was better and vice versa when the satisfaction of users of SIAT was good. the higher it is. Keywords: system quality, information quality, service quality, usage intensity, user satisfaction.